The effect of the options backdating scandal on the stock-price performance of 110 accused companies - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2006)
Since academic scholars and the Wall Street Journal reported widespread evidence indicating that option grants to executives were backdated, an avalanche of news stories followed documenting this ever-widening corporate scandal. In this study we ask: "How do disclosures of backdating affect shareholder value?" We closely examine 110 companies listed in the Wall Street Journal's Perfect Payday webpage, collecting all news stories related to options backdating. We find that shareholders of these 110 companies suffer on average significant stock-price declines, ranging between 20% and 50%. Moreover, these losses do not seem to be due to temporary overreactions (at least so far). The negative 20% abnormal return translates into total dollar losses of well over $100 billion. The negative 50% abnormal return translates to approximately one-quarter trillion dollars of lost shareholder value. There is no evidence that this decline is driven by temporary overreaction, judging by the average performance of these 110 companies over a nearly 2 year period. We are aware of no analysts, scholars or commentators predicting that such massive losses in shareholder value would result from options backdating problems.